The association of four SNPs in DNA mismatch repair genes with idiopathic male infertility in northwest China. (24th July 2019) - Zhao, Xinyan; Mu, Chunlan; Ma, Jia; Dai, Xiaojing; Jiao, Haiyan
Abstract: DNA mismatch repair (MMR) plays a critical role in the maintenance of genetic integrity. The failure of MMR in sperm DNA was found in male infertility. However, its aetiology in idiopathic male infertility (IMI) remains unknown. The present study was to investigate whether the four SNPs (rs26279 in MSH3, rs1800734 and rs4647269 in MLH1 and rs175080 in MLH3 ) in MMR genes were associated with IMI or not. The interactions of the SNPs were also performed to clarify its genetic aetiology. In the present study, 209 clinically diagnosed IMI men and 201 fertile men were recruited. Four SNPs were genotyped by DNA sequencing. It was the first time to investigate the association between rs26279 in MSH3 and IMI. The genotype frequency distribution of rs26279 (A>G) in MSH3 was found to be significantly different between IMI and control ( p  < 0.05), as well as azoospermia. The rs1800734 and rs4647269 in MLH1 were found to be significantly different between severe oligozoospermia and control groups ( p  < 0.05). However, rs175080 in MLH3 was not significantly different between IMI and control ( p  > 0.05). Multifactor dimensionality reduction (MDR) for detecting interactions showed that there were no interactions among the four SNPs on IMI.